TOTAL ERYTHROCYTE COUNT AND HEMOGLOBIN IN BUFFALOES - A. Z. Durrani; N. Kamal; M. S. Khan (Journal of Animal and Plant Sciences, 2006)
A total of 600 animals were selected on the basis of the clinical findings (emaciation, anemia, difficulty in walking, shrinking of neck muscles, difficulty in rising up, sunken eyes, infertility, skin eczema) & presence of ticks on the body. The blood examination of these animals revealed 107 as positive (17.8%) cases of theileriosis. The overall incidence recorded in July 2003 was 15.5%, while in August and September 2003 it was 20.5 and 17.5%, respectively. In Jia Bagga village 18% incidence was recorded in July 2003 while in August and September 2003 the incidence was 22.7 and 19.4. In Jhadoo village the incidence recorded was 14.9% in July 2003 whereas in the months of August and September 2003 the incidence recorded were 18.18 and 16.4 respectively. The incidence in Ghang Sharif village were 13.4%, 21.2% and 16.4% during July, August and September 2003 respectively. A study of hematological parameters showed 12 that in Jia Bagga the mean values of PCV, total erythrocyte count and hemoglobin concentration were 0.18 l/l, 4 X10 12 and 65 gm/l, respectively. In Jhadoo these values were 0.16 l/l, 3.5 X10 and 69.5 gm/l, respectively and in Ghang 12 Sharif the values were 0.20 l/l, 3.5 X10 and 72.5 gm/l, respectively. The overall mean value of the three hematological 12 parameters namely PCV, total erythrocyte count and hemoglobin concentration were 0.15 l/l, 3 X10 and 64.5 gm/l respectively. Comparison of these recorded values and normal values in buffalo showed that there was marked decrease in the PCV, total erythrocyte count and hemoglobin concentration in buffaloes suffering from theileriosis in union council Jia Bagga District Lahore. The difference between normal and infected animal blood parameter values were found to be statistically significant. skins. According to Ministry of Food, Agriculture and
Keywords: Theileriosis; packed cell volume; total erythrocyte count; hemoglobin; buffalo.